An Exploratory Study On Centralized Cryptocurrency As An Alternative Transactional System In Nigeria - Alhaji, Saidu Sani (2022)
This study is aimed at assessing the operation of the current fiat and fractional reserve transactional system and the possibility of adopting an centralized cryptocurrency as an alternative transactional system that should go a long way in minimising rising cost of living, consistent recession, repeated economic crisis, overwhelming increase in debt and devastating household living condition and general economic instability. The quantity theory of money, modern monetary theory and unified theory of acceptance and usage of technology was used support the study variables usage and to also straighten the study findings. The study adopts a sequential explanatory mixed mode method of research where the study data was collected through quantitative and qualitative means of data collection. The study uses Nigeria as the study area which was selected using purposive sampling technique. The quantitative data was gathered from publish World Bank data, IMF data and Central Bank of Nigeria report on the monetary and microeconomic variables for the study period 1973-2020. On the hand, the qualitative information was collected using a semi-structured interview questions from the sampled participants. The collected data and information from quantitative and qualitative sources was analysed using MINITAB 16 and AtlasTi.